LEPROSY IN MATO GROSSO DO SUL: : A SPATIAL, SOCIOECONOMIC AND IMPACT VIEW OF THE COVID-19 PANDEMIC - Caserta Tencatt-Abrita, Ana Paula; Boldrine Abrita, Mateus (GEOFRONTER, 2024)
This paper analyzes leprosy indicators in the state of Mato Grosso do Sul (MS), Brazil, emphasizing the socioeconomic and spatial elements, and compare the pre and post-Covid-19 pandemic periods. This study hypothesizes that leprosy substantially influences the socioeconomic aspects and that the pandemic period has impacted the notifications of the disease. The analyses demonstrated an overall decline in leprosy notifications in the comparison before and after the Covid-19 pandemic. The proportion of new cases of leprosy classified as stage II of physical disability at the time of diagnosis got worse. The disease presents a strong socioeconomic relationship, given both the disease’s biological favoring in vulnerable environments and the negative impact that it can cause on the economic scope of the affected ones, such as labor limitations, prejudice, and disabilities, resulting in negative socioeconomic feedback.